Floral colour variation of Nicotiana glauca in native and non-native ranges: Testing the role of pollinators' perception and abiotic factors - Costa, Antonella (2023)
Invasive plants displaying disparate pollination environments and abiotic conditions in native and non-native ranges provide ideal systems to test the role of different ecological factors driving flower colour variation. We quantified corolla reflectance of the ornithophilous South American Nicotiana glauca in native populations, where plants are pollinated by hummingbirds, and in populations from two invaded regions: South Africa, where plants are pollinated by sunbirds, and the Balearic island of Mallorca, where plants reproduce by selfing. Using visual modelling we examined how corolla reflectance could be perceived by floral visitors present in each region. Through Mantel tests we assessed a possible association between flower colour and different abiotic factors. Corolla reflectance variation (mainly along medium to long wavelengths, i.e. human green-yellow to red colours) was greater among studied regions than within them. Flower colour was more similar between South America and South Africa, which share birds as pollinators. Within invaded regions, corolla reflectance variation was lower in South Africa, where populations could not be distinguished from each other by sunbirds, than in Spain, where populations could be distinguished from each other by their occasional visitors. Differences in corolla colour among populations were partially associated with differences in temperature. Our findings suggest that shifts in flower colour of N. glauca across native and invaded ranges could be shaped by changes in both pollination environment and climatic factors. This is the first study on plant invasions considering visual perception of different pollinators and abiotic drivers of flower colour variation.